Philippine-Middle East Relations: Prospects and Challenges amidst ASEAN and China Engagement - Sevilla, Henelito (Nation State: Journal of International Studies, 2024)
The countries in the Persian Gulf highly intertwined with the global economy. Given its strategic location and abundance of resources, the Persian Gulf countries (GCC) is expected to play a critical role in the future economic direction and stability of the Middle East and Asian region. Liberal reforms instituted by GCC such as the Kingdom of Saudi Arabia and the United Arab Emirates (UAE) and other non-traditional partners wield significant influence. This development calls for a re-evaluation of policies by regional actors and domineering global powers with a stake in the region such as the United States (US). These GCC reforms open a new round of opportunities for countries in the Global South, particularly ASEAN member like Philippines. This paper seeks to evaluate the ongoing economic and geopolitical transformation in the Persian Gulf amid growing Chinese presence and GCC regimes’ economic reforms. Furthermore, this paper poses question, how the Philippines can use an independent foreign policy and take advantage of the changing political-economy landscape in the Middle East. This further suggest that the time is ripe for the Philippines to rethink its strategic policy toward the GCC and the Middle East to maximize gains outside of the US alliance system.